The Impact of Specific Gut Microbiota Metabolites on Chronic Kidney Disease Progression: Novel Diagnostic Biomarkers and Therapeutic Targets - Dąbkowska, Daria; Mioskowska, Agnieszka; Szydziak, Joanna; Hrapkowicz, Aleksandra; Janowska, Kinga; Szeidl, Olga; Rehan, Dominika; Wołoszczak, Julia (Journal of Education, Health and Sport, 2025)
Introduction: Chronic kidney disease is characterized by an irreversible and gradually progressive process. Recent research has highlighted the role of metabolites derived from the intestinal microbiota as important factors in the progression of this disease. Consequently, numerous studies have focused on the impact of the microbiota, its diagnostic potential, and its therapeutic applications. Aim of the study: This study highlights the role of specific gut microbiota in chronic kidney disease and its potential applications in diagnosis and therapy. Material and methods: An English-language literature review was conducted, analyzing studies from the PubMed database up to December 2024 regarding the correlation between specific gut microbiota and chronic kidney disease. The review was performed using the PubMed database, with 57 works used. Conclusion: Chronic kidney disease is characterized by a slow, progressive, and irreversible decline in kidney function. Recent studies have highlighted the significant role of metabolites produced by the intestinal microbiota in the progression of this disease. Consequently, extensive research has been conducted on the impact of these metabolites for diagnostic purposes as well as their potential therapeutic applications. These metabolites can aid in both diagnosing the condition and predicting its progression. Emerging therapies that manipulate the microbiota—through approaches such as dietary changes, probiotics, modulation of bacterial metabolites, fecal microbiota transplantation, or the use of genetically modified bacteria—have shown promising results. However, further research is essential to fully develop and refine these therapeutic strategies.